Potensi Ekonomi Berbasis Warisan Keulamaan: Studi atas Peninggalan Syekh Nawawi al-Bantani di Tanara, Kabupaten Serang - Ubay Haki; Fidziah Fidziah; Eka Danik Prahastiwi (Lembaga Yasin AlSys, 2026)
The intellectual and religious legacy of Syekh Nawawi al-Bantani in Tanara, Serang Regency, possesses high historical, religious, and social value and has the potential to become a driver of the local economy through the development of religious tourism, empowerment of micro, small, and medium enterprises (MSMEs), and the strengthening of community-based economic initiatives. This study aims to analyze the economic potential that can be developed from the heritage sites of Syekh Nawawi al-Bantani in Tanara and to identify sustainable development strategies grounded in local wisdom. The research employed a descriptive qualitative method through field observations, interviews with community leaders, site managers, and MSME actors, as well as a review of relevant literature. The findings show that the legacy of Syekh Nawawi al-Bantani has become a magnet for religious visits that stimulate increased economic activity in the culinary, handicraft, and service sectors, while community-based management patterns generate relatively inclusive economic impacts for local residents. The study concludes that strengthening the governance of religious tourism, enhancing the capacity of MSME actors, and fostering synergy between local government, academics, and the local community are key strategies to sustainably optimize the economic potential of the heritage sites of Syekh Nawawi al-Bantani, while simultaneously reinforcing the socio-religious ecology and community-based economy in Tanara.